2020
DOI: 10.3390/bios10090122
|View full text |Cite
|
Sign up to set email alerts
|

Silver-Based SERS Pico-Molar Adenine Sensor

Abstract: Adenine is an important molecule for biomedical and agricultural research and applications. The detection of low concentration adenine molecules is thus desirable. Surface-enhanced Raman scattering (SERS) is a promising label-free detection and fingerprinting technique for molecules of significance. A novel SERS sensor made of clusters of silver nanostructures deposited on copper bumps in valleys of an etched silicon substrate was previously reported to exhibit a low and reproducible detection limit for a 10−1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…It is worth noticing that, according to Ref. 45 ,an increase of the measured EF (up to almost an order of magnitude) can be obtained by increasing the buffer pH value from 7 to 9.…”
Section: Resultsmentioning
confidence: 83%
“…It is worth noticing that, according to Ref. 45 ,an increase of the measured EF (up to almost an order of magnitude) can be obtained by increasing the buffer pH value from 7 to 9.…”
Section: Resultsmentioning
confidence: 83%
“…Surface-enhanced Raman spectroscopy/scattering (SERS) is one of the most fascinating analytic techniques for rapid, in-field, single-shot detection of analyte molecules finding impending applications in biomedicine, clinical, environmental detection, food safety, and so forth. ( Vendamani et al, 2022 ; Verma and Soni, 2022 ; Tzeng and Lin, 2020 ; Zhang et al., 2013 ; Powell et al., 2017 ; Ouyang et al., 2018 ; Xu et al., 2018 ; Zhu et al., 2021 ). This technique has also been favored in food inspection via examining antibiotic deposits in animal products ( Lirio et al., 2016 ; Li et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous SERS studies have been conducted to detect this molecule and one of the best reported LOD was achieved by Tzeng and Lin who could detect down to 10 picomolar neutral adenine solutions with good reproducibility by using Ag@Cu@Si substrate. Further, 1 picomolar detection was achieved with the same substrate by taking SERS measurements of the aqueous adenine solution at a pH of 9 [ 266 ]. Other silicon-based substrates such as AgNC@SiO 2 on a polymethylhydrosiloxane modified filter paper and AuNP@FePt@SiO 2 demonstrated the enhancement by 6–7 orders of magnitude and LOD of about 1 nM [ 101 , 231 ].…”
Section: Performance Comparison With Gold and Silver Substratesmentioning
confidence: 99%